2022
DOI: 10.1093/jxb/erac441
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate-regulated root growth inhibition and root hair elongation

Abstract: The phytohormone jasmonate is an essential endogenous signal to regulate multiple plant processes for environmental adaptations, such as primary root growth inhibition and root hair elongation. Perception of environmental stresses promotes the accumulation of jasmonate which is sensed by the CORONATINE INSENSITIVE1 (COI1)-JASMONATE ZIM-DOMAIN (JAZ) co-receptor, triggering the degradation of JAZ repressors and induction of transcriptional reprogramming. The basic helix-loop-helix (bHLH) subgroup IIIe transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 123 publications
(172 reference statements)
0
10
0
Order By: Relevance
“…In addition, several types of JAs showed differential accumulation in the arrowhead samples from the two treatment groups. When plants were stressed, JA increased and interacted with other hormones, and inhibiting root elongation was also a typical trait [42]. Therefore, we speculated that JA may be involved in the rhizosphere pressure response in the underground parts, which provides new evidence of JA signals mediating rhizosphere pressure to change rhizosphere characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, several types of JAs showed differential accumulation in the arrowhead samples from the two treatment groups. When plants were stressed, JA increased and interacted with other hormones, and inhibiting root elongation was also a typical trait [42]. Therefore, we speculated that JA may be involved in the rhizosphere pressure response in the underground parts, which provides new evidence of JA signals mediating rhizosphere pressure to change rhizosphere characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…The term “jasmonates” generally refers to jasmonic acid and its derivatives, typically including jasmonyl isoleucine (JA-Ile) and methyl jasmonate (MeJA) [ 27 ]. In addition to its well-known role in growth and development, and in defense against pathogen attack and insect herbivory [ 28 , 29 , 30 , 31 , 32 ], a growing number of studies have highlighted the vital role of JA in the response to a variety of abiotic stresses, including drought, salinity, heat, and cold stress response [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the present review, we present recent findings regarding the role of JA in the response to cold and heat stress, and we elucidate the major components in the JA signaling pathway that are involved in cold and heat stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Roots and root hairs are unique organs for anchoring plants in the soil and absorbing water and nutrients, and Han et al (2023) review novel findings in the control of their development by jasmonate. Inhibition of root growth is a hallmark phenotype for screening of jasmonate-related mutants, and studies have shown that MYC2 is a positive regulator for this response ( Lorenzo et al , 2004 ).…”
mentioning
confidence: 99%
“…bHLH3 and bHLH17) negatively regulate root growth inhibition through physically interacting with JAZ proteins. Jasmonate also stimulates root-hair development, and ( Han et al (2023) first ­introduce the research background and then highlight the recent finding that JAZ proteins interact with and inhibit the RHD6 and RSL4 transcription factors to control root-hair elongation. Previous reports have shown that two ethylene-activated transcription factors, EIN3 and EIL1, interact with JAZ proteins and participate in the regulation of root-hair growth ( Zhu et al , 2011 ).…”
mentioning
confidence: 99%